To Be, To Move, To React: Reflections on possible neo-postcolonial readings of the African agency - Stoica, Diana Sfetlana (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Focusing on African agency, this paper debates around a constructed triad of concepts found at the roots of African ways of expressing the struggle for identification, recognition and also the rise of a continent in worldly discourses, in a holistic and rather philosophical approach. The constructed triad is represented by narratives of dynamic verbs such as to be, to move and to react, in a post-structuralist intent to express the concept of following Africa, an alternative token for the changes in the perception of African agency. The aim of this concept is to symbolize, in a neo-postcolonial reading, the consciousness of self-consciousness, as a possible complex process of African becoming and the African continent’s rise in the global narratives.